2023
DOI: 10.3390/biomechanics3010010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on the Trunk and Lower Limb Kinematics during Gait on a Compliant Surface in Healthy Individuals

Abstract: Older adults have a smaller effective living space and reduced physical activity. Although walking ability in various living spaces is necessary to maintain a healthy life and a high level of physical activity, it is unclear how older adults adapt to compliant surfaces when walking. The purpose of this study was to determine the differences in the trunk and lower limb kinematics while walking on a level versus compliant surface, and the effect of aging on these kinematic changes. Twenty-two healthy individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Single-leg balance performance was the desired outcome of the present study. It was interesting as this represents a vital phase in the gait cycle (i.e., single-support) where individuals are at high risk for stability loss (Honda et al, 2023;Riva et al, 2013). Several studies have indicated that the single-support phase of the gait cycle, particularly among older adults in the seventh and eighth decade, requires more intervention.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Single-leg balance performance was the desired outcome of the present study. It was interesting as this represents a vital phase in the gait cycle (i.e., single-support) where individuals are at high risk for stability loss (Honda et al, 2023;Riva et al, 2013). Several studies have indicated that the single-support phase of the gait cycle, particularly among older adults in the seventh and eighth decade, requires more intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that the single-support phase of the gait cycle, particularly among older adults in the seventh and eighth decade, requires more intervention. As mentioned, this is mainly due to significant decreases in single-support phase duration, leading to gait modifications that can increase the risk for balance loss (Honda et al, 2023;Murray et al, 1969). Although only college-aged participants were involved in the present study, the experimental design must assess the efficacy and feasibility of utilizing positive and negative self-talk to enhance balance performance in at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations